Penguatan Literasi Digital Guru Sekolah Dasar melalui Penyusunan Bahan Ajar dan Asesmen Berbantuan AI - Melia Hansa Cordelia Tabina; Freynaya Echa Naylarega; Sinta Novita Ramandani; Anisa Vella Farda; Muhammad Arib Rif’an; Rani Setiawaty (Muria Jurnal Layanan Masyarakat, 2025)
This community service program aims to examine the effectiveness of teacher training in improving literacy learning quality through the utilization of artificial intelligence (AI)-based technology. The training was conducted faceto-face, focusing on the development of digital teaching materials and interactive assessments using Gamma AI and Educaplay. The results showed an increased understanding among teachers regarding the integration of technology into the learning process, as well as the production of innovative and interactive learning materials. Positive responses from participants indicate that this training was effective in enhancing teachers’ pedagogical competence and the overall quality of literacy learning. The integration of AI has proven to be an adaptive and relevant strategy to support the improvement of basic education quality in the digital era. Pengabdian kepada masyarakat ini bertujuan mengkaji efektivitas pelatihan guru dalam meningkatkan kualitas pembelajaran literasi melalui pemanfaatan teknologi berbasis kecerdasan buatan (AI). Pelatihan dilaksanakan secara tatap muka dengan fokus pada penyusunan bahan ajar digital dan pengembangan asesmen interaktif menggunakan Gamma AI dan Educaplay. Hasil kegiatan menunjukkan peningkatan pemahaman guru terhadap integrasi teknologi dalam proses pembelajaran serta terciptanya produk bahan ajar yang inovatif dan interaktif. Respon positif peserta menegaskan bahwa pelatihan ini efektif dalam meningkatkan kompetensi pedagogik dan kualitas pembelajaran literasi. Integrasi AI terbukti menjadi strategi yang adaptif dan relevan dalam mendukung peningkatan mutu pendidikan dasar di era digital.